The COMPARE Data Hubs. (23rd December 2019) - Amid, Clara; Pakseresht, Nima; Silvester, Nicole; Jayathilaka, Suran; Lund, Ole; Dynovski, Lukasz D; Pataki, Bálint Á; Visontai, Dávid; Xavier, Basil Britto; Alako, Blaise T F; Belka, Ariane; Cisneros, Jose L B; et al.
Abstract: Data sharing enables research communities to exchange findings and build upon the knowledge that arises from their discoveries. Areas of public and animal health as well as food safety would benefit from rapid data sharing when it comes to emergencies. However, ethical, regulatory and institutional challenges, as well as lack of suitable platforms which provide an infrastructure for data sharing in structured formats, often lead to data not being shared or at most shared in form of supplementary materials in journal publications. Here, we describe an informatics platform that includes workflows for structured data storage, managing and pre-publication sharing of pathogen sequencing data and its analysis interpretations with relevant stakeholders.